The Ninjabread Man - Leigh, C. J.; Gall, Chris (New York : Orchard Books, an imprint of Scholastic Inc., 2016)
In this adaptation of the traditional Gingerbread man, Ninjabread Man escapes the Sensei, and tries to outsmart Ninja Bear, Ninja Snake, Ninja Mouse, and Ninja Fox.
Keywords: Gingerbread men -- Adaptations -- Juvenile fiction; Gingerbread men -- Adaptations -- Fiction; Ninja -- Juvenile fiction; Animals -- Juvenile fiction; Martial arts -- Juvenile fiction; Cookies -- Juvenile fiction; Folklore